2019
DOI: 10.3390/children7010001
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Safety of Polysorbates in Drug Formulations

Abstract: Polysorbates 20 and 80 are the most frequently used excipients in biotherapeutics, the safety data for which have been well documented in adults. The polysorbate content in therapeutic formulations that are administered to children, however, has been less clearly regulated or defined with regard to safety. In pediatric patients, excessive amounts of polysorbate in biotherapeutics have been linked to hypersensitivity and other toxicity-related effects. To determine safe levels of polysorbates for young patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
(37 reference statements)
0
29
0
Order By: Relevance
“…Indeed, the pharmacokinetic and pharmacodynamic profiles of the child population vary substantially, with paediatric safety profiles related to the age and development of excipients often differing from those of adults [ 48 ]. The most toxic excipients in neonates are known to be sodium benzoate, propylene glycol, methyl para hydroxybenzoate, propyl, sodium saccharine, benzyl alcohol, benzalkonium chloride, polysorbate 80 and ethanol [ 56 ]. However, these excipients are used in formulations according to the study conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the pharmacokinetic and pharmacodynamic profiles of the child population vary substantially, with paediatric safety profiles related to the age and development of excipients often differing from those of adults [ 48 ]. The most toxic excipients in neonates are known to be sodium benzoate, propylene glycol, methyl para hydroxybenzoate, propyl, sodium saccharine, benzyl alcohol, benzalkonium chloride, polysorbate 80 and ethanol [ 56 ]. However, these excipients are used in formulations according to the study conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In Belgium, an initially healthy newborn experienced acute cardiogenic shock and multiple organ failure after receiving intravenous amiodarone with polysorbate excipient at a loading dose (47 mg/kg) that was intended for oral administration. 69 Polysorbate 20 and 80 are also surfactants commonly used in protein parenteral formulations to minimize denaturation at the air-water interface. It is also sometimes used in injectable solutions of small molecules for the purpose of solubility enhancement due to its ability to form micelle.…”
Section: Polysorbatesmentioning
confidence: 99%
“…Parenteral administration of more than 50.6 g polysorbate 80 and 3.37 g polysorbate 20 in biotherapeutics have been linked to hypersensitivity and other toxicity-related effects such as thrombocytopenia, cholestasis, ascites, hypotension, renal dysfunction, hepatomegaly, and severe metabolic acidosis which may lead to death. 69 Polysorbates are also found to inhibit the activity of P-glycoproteins (P-gp) which are efflux transporters of absorbed drugs. 68 For instance, a study done by Zhang et al, 70 showed that the blood concentration of orally administered digoxin was increased by 61% when polysorbate was used concomitantly.…”
Section: Polysorbatesmentioning
confidence: 99%
See 2 more Smart Citations